ANALISA UNJUK KERJA MESIN DIESEL KAPASITAS 132cc PADA PROTOTIPE CULA SATU UNTIRTA - Imron Rosyadi; Agung Sudrajat; Teguh Perkasa Alam (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2015)
Indonesia Energy Marathon Challenge (IEMC) is an activity held to test the ability of designing and building vehicles that are safe, efficient and environmentally friendly. Cula Satu Untirta were the work of students of Untirta Mechanical Engineering who has followed IEMC competition in 2013. This vehicle uses 4 stroke diesel engine which has a capacity of 210 cc. However, from the use of large-capacity diesel engine that it acquired less than optimal results, due to the large cylinder capacity can affect fuel use is becoming increasingly large.This is the purpose of the writer to manage the use of fuel consumption on the machine which has a capacity of 210 cc by modifying the cylinder volume of the decline from 210cc to 132cc. From testing using three fuels (Pertamina Dex, Shell and Total diesel diesel) obtained as a result of that Shell has diesel torque, power and low fuel consumption with maximum torque set at 1,800 rpm engine with engine rotation value of 8.76 Nm, as well as maximum power at 2000 rpm with a value of 2.36 hp. On lap 1600 rpm with load on handles 0.56 kg, Daya 1.86 hp which can reach time 204.66 seconds.